Açai pulp supplementation as a nutritional strategy to prevent oxidative damage, improve oxidative status, and modulate blood lactate of male cyclists - Terrazas, Sara Ivone Barros Morhy [UNESP]; Galan, Bryan Steve Martinez [UNESP]; De Carvalho, Flávia Giolo; Venancio, Vinicius Paula; Antunes, Lusânia Maria Greggi; Papoti, Marcelo; Toro, Maricely Janette Uria; da Costa, Iuri Ferreira; de Freitas, Ellen Cristini [UNESP] (Springer Nature, 2020)
Purpose: Açai pulp is a source of phytochemicals and has been associated with antioxidant, anti-inflammatory, and antigenotoxic effects. This study aimed to assess the effects of açai pulp consumption on oxidative, inflammatory, and aerobic capacity markers of cyclist athletes. Research methods and procedures: A crossover, randomized, placebo-controlled, single-blind study was developed with ten male cyclists (33.5 ± 4.7 years old, body mass index of 23.9 ± 1.38 kg/m2, and training load around 1875 ± 238 AU/week). The athletes consumed 400 g/day of pasteurized açai pulp (AP) or placebo (PL) for 15 days, with a 30-day wash-out period between trials. Lipid peroxidation, serum antioxidant capacity, DNA damage in peripheral blood (Comet assay), IL-6 and TNF-alpha, blood lactate concentration during effort, anaerobic threshold intensity (ATi), maximum workload reached (Wmax), rating of perceived exertion threshold (RPET), and heart rate threshold (HRT) were evaluated before and after each intervention. Data were analyzed using a linear regression model with mixed effects (p ≤ 0.05). Results: Increased serum antioxidant capacity (p = 0.006) and decreased lipid peroxidation (p = 0.01) were observed in subjects after intervention with AP. Blood lactate levels during effort significantly decreased (by 29%, p = 0.025) and ATi increased (p = 0.006) after AP. No significant effect on DNA damage was attributed to AP consumption. Conclusion: We found notable effects of AP intervention on antioxidant status in athletes. Both the reduction in blood lactate concentration and increase in ATi during the effort suggest an overall improvement in the aerobic capacity of the cyclists, confirming that AP consumption may influence variables associated with performance in endurance athletes.
Keywords: Anthocyanins; Antioxidant; Athletes; Açai; DNA damage